Tantangan dalam Implementasi Kurikulum Merdeka di SD N 060851 Jl. Madong Lubis No. 1, Sei Kera Hilir II (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study examines the challenges in implementing the Independent Curriculum at SD N 060851, Medan, North Sumatra. Through a case study of a teacher, this study reveals obstacles such as teacher understanding of the curriculum, training effectiveness, student engagement, and school resource readiness. This study also shows teacher adaptation strategies to the curriculum. The findings suggest that successful implementation of the Independent Curriculum requires addressing these challenges through targeted training, increased support for teachers, and better access to resources.